2009
DOI: 10.1097/ta.0b013e3181b5ae75
|View full text |Cite
|
Sign up to set email alerts
|

Testing of Blood Products in a Polytrauma Model: Results of a Multi-Institutional Randomized Preclinical Trial

Abstract: In this reproducible model, we have shown that trauma-associated coagulopathy is made worse by hetastarch, but it can be rapidly reversed with the administration of blood components. Impressively, infusion of FFP, even without any red blood cells, can correct the coagulopathy and result in excellent early survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 24 publications
1
35
0
3
Order By: Relevance
“…2,39 Plasma is the treatment of choice to prevent or mitigate coagulopathy in trauma patients; even in the absence of transfused erythrocytes its use was shown in an animal model to be superior to a colloid at reversing the coagulopathy of trauma and to improve survival. 40 The availability of FLyP in austere settings, as well as in prehospital units, could benefit severe trauma patients, and its use could be extended to civilian centers. However, strong evidence is lacking regarding the wide use of FLyP in emergency settings, and clinical trials should be promoted to address the issue of a benefit of the use of FLyP instead of thawed FFP.…”
Section: Critical Care Medicinementioning
confidence: 99%
“…2,39 Plasma is the treatment of choice to prevent or mitigate coagulopathy in trauma patients; even in the absence of transfused erythrocytes its use was shown in an animal model to be superior to a colloid at reversing the coagulopathy of trauma and to improve survival. 40 The availability of FLyP in austere settings, as well as in prehospital units, could benefit severe trauma patients, and its use could be extended to civilian centers. However, strong evidence is lacking regarding the wide use of FLyP in emergency settings, and clinical trials should be promoted to address the issue of a benefit of the use of FLyP instead of thawed FFP.…”
Section: Critical Care Medicinementioning
confidence: 99%
“…Zaar et al 17 used liver damage in 30-kg pigs which caused a moderately large Alam et al 18 subjected pigs to femur fracture, controlled hemorrhage, and finally to liver damage. In this complex model resuscitation with 6% hetastarch (MW 600 kD, Hextend) resulted in 85% mortality while fresh whole blood, fresh frozen plasma with and without red blood cells in the ratio 1:1 were followed by 100% survival.…”
Section: Starchmentioning
confidence: 99%
“…A recent process improvement project that was conducted in theater among evacuation units in Afghanistan showed that nearly all casualties transported received a routine infusion of crystalloids and that less than 10% of those with significant hemorrhage received the appropriate fluid therapy in accordance with tactical combat casualty care (TCCC) guidelines. 26 According to Alam et al, 27 infusion of large amount of crystalloids can result in significant lactic acidosis, dilutional anemia, and thrombocytopenia. Also according to Alam et al, 27 large doses of hetastarch fluid in trauma patients could result in worsening coagulopathy.…”
Section: Discussionmentioning
confidence: 99%
“…26 According to Alam et al, 27 infusion of large amount of crystalloids can result in significant lactic acidosis, dilutional anemia, and thrombocytopenia. Also according to Alam et al, 27 large doses of hetastarch fluid in trauma patients could result in worsening coagulopathy. Another reason for a discrepancy in the fluid management is that the CCFP group not only had formalized certification, didactics, and hands-on training, but also had 9 years of trauma experience.…”
Section: Discussionmentioning
confidence: 99%